High-powered investing all-in-one for dummies - Best, Jason W. (--For dummies., 2014)
Looking for help making smarter, more profitable high-end investment decisions? This resource arms you with an arsenal of advanced investing techniques, and gets you up to speed on using business fundamentals and technical analysis to make smarter decisions and maximize your returns.